High transfection efficiency of neural stem cells with magnetofection. (March 2011) - Sapet, Cédric; Laurent, Nicolas; de Chevigny, Antoine; Gourrierec, Loïc Le; Bertosio, Elodie; Zelphati, Olivier; Béclin, Christophe
Primary neural stem cells (NSCs) can be cultivated and differentiated in vitro but are difficult to transfect using conventional methods. We describe a simple and rapid magnetofection-based method suitable for the lab bench as well as for high-throughput projects. Our method yields high transfection efficiency and can be used for deciphering the genetic control of neural cell differentiation.